1991
DOI: 10.3347/kjp.1991.29.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous fascioliasis: a case report

Abstract: A 32-year old housewife, living in Seoul, recognized incidentally a painless mass at the left chest wall. During later 3 months, she experienced spontaneous swelling and regression of the mass repeatedly for 4 times. Surgical resection showed a granuloma at anterior serratus muscle containing a nearly matured adult of Fasciola species without vitellaria and uterus. This is the 11th human fascioliasis and the first extra-abdominal infection reported in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Some reports have confirmed the migration of juvenile Fasciola spp. (Lee et al 1982;Chang et al 1991), also existence of gravid Fasciola in some organs was reported based on observation of tissue-embedded ova (Yazici et al 2005;Naresh et al 2006;Makay et al 2007;Ongoren et al 2009). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports have confirmed the migration of juvenile Fasciola spp. (Lee et al 1982;Chang et al 1991), also existence of gravid Fasciola in some organs was reported based on observation of tissue-embedded ova (Yazici et al 2005;Naresh et al 2006;Makay et al 2007;Ongoren et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Ectopic fascioliasis usually caused by juvenile Fasciola spp. (Lee et al 1982;Chang et al 1991;Zali et al 2004;Yi-Zhu and Zhi-Bang 2010), but in recent years a few cases of tissue-embedded ova have been reported from different areas (Yazici et al 2005;Naresh et al 2006;Makay et al 2007;Marcos et al 2009;Ongoren et al 2009). In this report, an unusual manifestation of ectopic fascioliasis in peritoneum is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Organised haematomas can occur in many locations, and they might be mistaken for soft tissue malignancies (Hsu and others 2009) and sometimes even with ectopic trematode parasites (Chang and others 1991, Madarame and others 2009). …”
Section: Differential Diagnosismentioning
confidence: 99%
“…Likewise, no invasive feature was observed either macroscopically or microscopically in the presented case. Ectopic parasites, in particular trematode parasites, are located subcutaneously at aberrant sites of the body in human beings (Chang and others 1991) and animals (Madarame and others 2009). Even if an organised haematoma looks like a trematode parasite in form, an organised haematoma has many different dimensions in the accumulated region, whereas a trematode parasite has similar dimensions.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…They were also found in lungs, heart, eyes, brain, and lymph nodes. [1][2][3][4][5][6] The first two cases of human fascioliasis were reported in Vietnam in 1978. Subsequently, infection with large liver flukes was frequently found in humans.…”
Section: Introductionmentioning
confidence: 99%